Pengaruh anggaran berbasis kinerja, transparansi, dan akuntabilitas, terhadap kinerja pegawai di Badan Pengelolaan Keuangan dan Aset Daerah Kabupaten Kepulauan Talaud - Arseta Maparipe; Jenny Morasa; Peter M Kapojos (Riset Akuntansi dan Portofolio Investasi, 2026)
This study aims to examine the effect of performance-based budgeting, transparency, and accountability on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of the Talaud Islands Regency. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 49 employees of BPKAD Talaud Islands Regency. The data were analyzed using multiple linear regression. The results indicate that performance-based budgeting does not have a significant effect on employee performance. In contrast, transparency and accountability have a positive and significant effect on employee performance. Simultaneously, performance-based budgeting, transparency, and accountability significantly influence employee performance. These findings highlight the importance of strengthening transparency and accountability practices in local government financial management to improve the performance of public sector employees.